Assessing Site Selection of subway routes of the metropolis of Tabriz for natural hazards with an emphasis on flood and earthquake - Hassan Mahmoudzadeh; Ahdiyeh Mousazadeh (مخاطرات محیط طبیعی, 2020)
The public transport system, such as Metro, has been created for the rapid and easy movement of passengers due to population growth in recent decades. Tabriz is one of Iran's cities with a subway system as well. The existence of Tabriz's fault in the north of Tabriz as the biggest threat fault in northwestern Iran and as a result of severe flooding in many of the country's cities this year, it seems necessary to assess the risks on the subway routes and stations in Tabriz. Combined flood and earthquake risk maps were prepared using FUZZY-AHP to have a comprehensive overview of the status of hazards. The purpose of this study was to identify flood and earthquake risk using 10 flood risk criteria and 14 earthquake risk criteria in the study area metro lines and stations. According to the final results of the flood risk zoning, there is no station in the very low-risk class, but there are 203,621 meters of low-risk subway lines, 5 stations and 6013,768 meters of high-risk subway lines. It also has 2 stations and 2454,91 meters of low-risk subway lines and 2 stations and 722,898 meters of high-risk subway lines, which make it necessary to identify and link stations with a potential risk of occurrence.